Examining strings program in school: profiling and recommendation / Muhamad Zulakmal Zaidi - Zaidi, Muhamad Zulakmal (2019)
The purpose of the study is to examine the current profile of school string program. The purpose of this study is to identify the teaching techniques, method books also other resources that string teachers used and to identify the playing problems faced by the teachers during teaching the strings ensemble. The findings of this study will help us to know what is happening to the development of strings program in schools and give benefit to the school teachers as it will help them to know and learn the suitable methods that can be used, and know the type of method used by a good string orchestra teacher in school. Thus, these methods also can help the students to improve their ability to play strings instruments either in individual skills or playing in ensemble skills. Furthermore, this study can be an additional reference for other researchers that have the same interest and improve it to make it better. The result on finding indicated a wide range about the usage of different method books on teaching the strings in schools. It is also to identify the problem faced by the teacher to teach strings instruments.